THE RELATIONSHIP OF PEER SUPPORT WITH BREAST SELF EXAMINATION BEHAVIOR IN ADOLESCENT WOMEN - Sukmawati, Sukmawati; Yuliani, Lala; Nurhakim, Furkon; Mamuroh, Lilis; Widiasih, Restuning (Universitas Aisyah Pringsewu, 2024)
Breast cancer is the highest case in women every year. Breast cancer can attack all age groups including adolescents. Breast self-examination behavior (BSE) is one of the most effective methods of early detection of breast cancer. One of the factors that influence the practice of BSE in young women is peer support. Aims: to determine the relationship of peer support with breast self-examination behavior (BSE) in adolescents. Design of this study was the descriptive correlational. The sample consisted of 219 students of SMAN Sumedang with proportionate random sampling technique. The instrument of this study was the BSE behavior and peer support questionnaires. The instrument was tested for validity and reliability, the result was a validity test 0.3 and a reliability test of 0.9. Result: the majority of respondents (80.8%) did not practice BSE, peer support to almost all teenage girls (91.3%) in the low support category. Peer support and BSE behavior in young girls had a significant relationship (sig. 2-tailed = 0,000). Based on the results of the study, it was concluded that the practice of BSE and peer support in teenage girls were in low category, there was a significant relationship between the two. It is hoped that health workers can collaborate with schools to provide continuous health education about the importance of BSE for young women.